INTERNALISASI NILAI - NILAI DASA DARMA PRAMUKA DALAM MEMBENTUK KARAKTER KEPRIBADIAN ISLAMI SISWA DI MI HIDAYATUS SHIBYAN NGASEM KEDIRI - Ali Ahmad Yenuri (MIYAH : Jurnal Studi Islam, 2021)
Abstract: The era of globalization demands advanced science and technology, but requires us to be wise in responding to it, because there are two positive and negative sides, especially the negative impact on moral degradation. This requires the teacher to the maximum in instilling character. problems related to moral degradation that still often occur everywhere. Various efforts have been made by the government to overcome this problem, one of which is by promoting character education. Many programs have been launched by the government related to improving the character of this nation, one of which is through the compulsory scout extracurricular program in schools. The basic values of the dharma of scouting in scouting activities are expected to produce quality characters, both in terms of reason, physical, and spiritual. internalization of dasa dharma values as the object of research. Existing problems are answered through qualitative research with data collection methods in the form of observation, interviews, and documentation. The data collected were analyzed qualitatively with the interactive analysis model of Miles & Huberman with data collection schemes, data reduction, data display and conclusions. The results of the study indicate that there is a relationship between the values of Dasa Dharma Scouts and Islamic characters, the process of internalizing the values of Dasa Dharma in scouting activities has an important role in realizing the Islamic character of students.Kata Kunci: Internalization, the value of dasa dharma scouts, Islamic character